Entrepreneurial Competencies in teaching-learning contexts: systematic literature review (2009-2020) (Management and Connections Journal, 2021)
The study aims to accomplish a systematic review of the literature on Entrepreneurial Competencies (EC) in training contexts, from 2009 to 2020. In this work, EC refer to higher-level characteristics, covering personality traits, skills and knowledge and, therefore, they can be seen as the total capacity of the entrepreneur to successfully perform a job function.Descriptors were used on the Capes journal portal and 27 national and international studies were selected, in which quantitative investigations prevail. And the antecedents investigations stand out. In 20 studies, instruments are used to measure EC. The authors assumed different theories to define the construct. The lack of consensus on this concept is evidenced by the variability in the number, from three to 40 factors, and in the naming of each one of the factors. Therefore, it is observed that EC are a promising construct for understanding entrepreneurship, but more studies are still needed.
Keywords: Entrepreneurial Competencies; Entrepreneurial Skills; Entrepreneurship; Competencies; Systematic Literature Review